LANDASAN PSIKOLOGIS PENGEMBANGAN KURIKULUM ABAD 21 - Ahmad Nur Kholik (AS-SALAM, 2019)
This article aims to examine the psychology foundations of 21st century curriculum development, because the foundation of psychology is one of the principles in curriculum creation and development. The method used in this research is literature study, collecting, analyzing, processing and presenting books, journals and texts related to the research theme as reference material in the form of literature reports. The rapid development of science and technology and the existence of free market competition between countries has implications for life and of course for the world of education. It is important to conduct a review of the principles of curriculum development, namely the psychological principles of students. The result of this research is that curriculum development must be based not only on philosophy but also based on psychology. In the 21st century with the rapid development of information and communication technology and free competition between countries in all fields will affect the psychology of students, This must be considered by curriculum developers so that orientation is no longer centered on cognitive but more on psychomotor or skills. This is why the foundation of psychology is very important in conducting curriculum development. The positive impact expected in this article for the world of education is for curriculum developers to focus more on the needs of students in the 21st century so that they can compete with other countries.